PENGARUH PEMBERIAN TUNJANGAN, KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - Muh. Jamsir Zibuka; Samdin Samdin; Nasrul Nasrul (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2018)
This study aims to examine and analyze empirically the effect of providing benefits, job satisfaction and work motivation on employee performance at the Muna Regency Regional Secretariat. This research is explanatory which intends to explain the position of the variables studied and the relationship and influence between one variable and another variable.The population in this study were all employees at the Muna Regency Regional Secretariat totaling 167 people. Determination of the number of samples in this study using the Slovin formula so that the number of samples was 63 people. This study uses multiple linear regression analysis.The results showed that: (1) Provision of benefits, job satisfaction and work motivation had a positive and significant effect on employee performance at the Muna Regency Regional Secretariat. For this reason, the first hypothesis in this study was accepted. (2) Provision of benefits has a positive and significant effect on employee performance at the Muna Regency Regional Secretariat. This can be interpreted that employees who receive the benefits also have high performance. For this reason, the second hypothesis in this study was accepted. (3) Job satisfaction has a positive and significant effect on employee performance at the Muna Regency Regional Secretariat. For this reason, the third hypothesis in this study was accepted. (4) Work motivation has a positive and significant effect on employee performance at the Muna Regency Regional Secretariat. For this reason, the fourth hypothesis in this study was accepted. Keywords: provision of allowances, job satisfaction, work motivation and employee performance